Thermal Field-Flow Fractionation of Polymers - Greyling, Guilaume; Pasch, Harald; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces the reader to thermal field-flow fractionation and discusses its advantages over the fundamental problems associated with traditional column-based analytical techniques commonly used to characterize polymers and macromolecules. The authors discuss the theoretical background, equipment, experimental procedures as well as the recent advances and applications of thermal field-flow fractionation. Complete with several practical examples and troubleshooting guidelines, the book is written for beginners and experienced separation scientists alike and will enable its readers to optimize their experimental conditions for their specific separation needs and problems.
Introduction -- Thermal Field-Flow Fractionation (ThFFF) -- Applications and Experimental Design -- Conclusions and Future Trends -- Troubleshooting.
Keywords: Polymers; Analytical chemistry; Polymers; Analytical Chemistry